2008
DOI: 10.1186/1478-7547-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating tuberculosis and HIV services for people living with HIV: Costs of the Zambian ProTEST Initiative

Abstract: BackgroundIn the face of the dual TB/HIV epidemic, the ProTEST Initiative was one of the first to demonstrate the feasibility of providing collaborative TB/HIV care for people living with HIV (PLWH) in poor settings. The ProTEST Initiative facilitated collaboration between service providers. Voluntary counselling and testing (VCT) acted as the entry point for services including TB screening and preventive therapy, clinical treatment for HIV-related disease, and home-based care (HBC), and a hospice. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…The cost per client tested for the home-based strategy was comparable to that (US$ 5.88 -8.29) reported in other studies [35][36][37] . Although the cost per client tested in the facility-based strategy reported here was higher than that of home-based VCT, it was lower than that reported elsewhere 31,36,38,39 . The level of care and range of services provided by a facility affects the costs and therefore contributes to the variation in costs observed.…”
Section: Discussioncontrasting
confidence: 47%
“…The cost per client tested for the home-based strategy was comparable to that (US$ 5.88 -8.29) reported in other studies [35][36][37] . Although the cost per client tested in the facility-based strategy reported here was higher than that of home-based VCT, it was lower than that reported elsewhere 31,36,38,39 . The level of care and range of services provided by a facility affects the costs and therefore contributes to the variation in costs observed.…”
Section: Discussioncontrasting
confidence: 47%
“…The Pro-TEST study in urban Zambia demonstrated that delivery of integrated services, including a strong referral system reduces patient costs and is financially feasible and inexpensive [17].…”
Section: Discussionmentioning
confidence: 99%
“…While treatment interruption during the course of TB treatment and antiretroviral treatment (ART) have been extensively studied [9]–[13], little is known about the linkage to care after the initial diagnosis [14], particularly among people diagnosed with HIV-associated TB at a hospital facility [15], [16]. Because the cost-effectiveness of diagnostic interventions is in part determined by successful linkage to care [17], [18], the rate of linkage to care should be monitored and evaluated along with other programmatic targets [18], [19]. Currently, rates of and reasons for failure to link TB and HIV diagnosis with care are not collected as part of routine monitoring and evaluation in TB and ART programs, making evidence-based decisions on how to improve linkage to care difficult [20].…”
Section: Introductionmentioning
confidence: 99%
“…2010) and tuberculosis (Harris et al . 2008; Terris-Prestholt et al . 2008), existing literature has paid far less attention to integration as it relates to service delivery at the primary level.…”
Section: Introductionmentioning
confidence: 99%